2009
DOI: 10.1080/10837450802662820
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and process development of (recombinant human) deoxyribonuclease I as a powder for inhalation

Abstract: A formulation and process development study was performed to formulate recombinant human deoxyribonuclease I as a powder for inhalation. First, excipient compatibility (with bovine DNase as a model substance) was examined with a stability study at stressed conditions (60 and 85 degrees C) while monitoring for occurrence of the Maillard reaction. Next, powders for inhalation were prepared by spray drying and spray freeze drying. We found that spray drying with inulin as stabilizer resulted in the best powder fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…The use of high temperatures during manufacturing of the implants may denature the antigen. However, in this study the implants were exposed to a temperature of 48 °C for a relatively short time (20 minutes), other studies showed that several proteins, such as DNAse [ 13 ], alkaline phosphatase [ 14 ], infliximab [ 15 ], hepatitis B surface antigen [ 11 ], and acyl-homoserine-lactone acylase [ 16 ] remained fully stable for several weeks at elevated temperatures (40–60 °C) when incorporated in inulin matrices. Hence, in this study the antigen was freeze-dried with inulin to stabilize the antigen.…”
Section: Resultsmentioning
confidence: 99%
“…The use of high temperatures during manufacturing of the implants may denature the antigen. However, in this study the implants were exposed to a temperature of 48 °C for a relatively short time (20 minutes), other studies showed that several proteins, such as DNAse [ 13 ], alkaline phosphatase [ 14 ], infliximab [ 15 ], hepatitis B surface antigen [ 11 ], and acyl-homoserine-lactone acylase [ 16 ] remained fully stable for several weeks at elevated temperatures (40–60 °C) when incorporated in inulin matrices. Hence, in this study the antigen was freeze-dried with inulin to stabilize the antigen.…”
Section: Resultsmentioning
confidence: 99%
“…This being given, it is not surprising that 174 inulin was shown to be a good stabilizer of proteins under various conditions and stresses. Inulin has 175 been successfully used to stabilize proteins during spray-drying (Grasmeijer et (Zijlstra, Ponsioen, et al, 2009). The number of reducing groups is dependent on processing and 182 DP and is generally limited (Mensink et al, 2015).…”
Section: Protein Stabilization 157mentioning
confidence: 99%
“…As mentioned inulin has a small amount of reducing groups, meaning some protein degradation 252 because of the Maillard reaction might occur. Yet even under extreme storage conditions (85 °C / 0%RH 253 / 42days) this only played a minor role in protein stability of rhDNase, a protein that is sensitive to this 254 type of degradation(Zijlstra, Ponsioen, et al, 2009). In summary, inulin is a good stabilizer of proteins in 255 the dry state, and depending on the formulation and storage conditions it can be better than membranes and proteins, inulin has also been used to stabilize several pharmaceutically260 relevant systems.…”
mentioning
confidence: 98%
“…However, the authors suggested that this drawback might be overcome by an improvement in the formulation design. In the present study, COLI-loaded particles for pulmonary inhalation were developed by using inulin (INU) as an excipient allowing particles with suitable aerodynamic properties to be formulated [25,26] and potentially reducing the irritating effects observed in humans with pure COLI sulfate. Additionally, INU was shown to be an excellent stabilizing agent for amorphous material due to its high glass transition temperature [27].…”
Section: Microparticle Formulation and Characterizationmentioning
confidence: 99%